The Status of Science Education Programs at Graduate Institutions Offering Only the Master's Degree. - Yager, Robert E. (Science Education, 1982)
The article discusses the status of education programs at graduate institutions offering only the Master's degree. Science education emerged as a major discipline in graduate institutions from 1960 to 1970 and continuing until 1975. The nature of Master's degree programs has remained rather stable during the 1960-1980 period. In addition, most of the graduate science education programs are designated as subunits of a curriculum and instruction department or a special program area, and few are formal department or centers.